Manajemen Deteksi Dini Faktor Resiko Penyakit Tidak Menular (PTM) - Rofiqoch, Isnaeni (Universitas Respati Yogyakarta, 2020)
Non-Communicable Diseases (NCD) is one of the causes of death in the world. Indonesia is a developing country that is facing a double burden of diseases, namely infectious diseases and non-communicable diseases. NCD can appear without symptoms and show no clinical signs, so many people are not aware of the dangers of NCD disease. The purpose of this comunity service is to provide counseling about NCD and measure blood pressure in an effort to detect NCD Early.This community service uses counseling as a method to increases partner knowledge in early detection of NCD. The average of partners knowledge increase by 42.6%. This is calculated by comparing the pre test average value of 5.70 and the post test average value of 8.20. Implementation of community service can increase the knowledge of the elderly posyandu group of Sokaraja Kulon Village so that the participants have the desire to prevent NCD and find out blood pressure from blood pressure measurement results in order to reduce the causes of non-communicable diseases (NCD) and have the intention to inform knowledge about Non-Communicable Diseases (NCD) to Family, Relatives and Communities.Keywords :Early Detection,Non-Communicable Diseases